Fiona's lace - Polacco, Patricia (New York : Simon & Schuster Books for Young Readers, 2014)
"Fiona and her family moved from Ireland to Chicago to begin a new life. Yet, when the family is struck with misfortune, will Fiona's lace help save them?"--Provided by publisher.
"A Paula Wiseman Book"--T.p.
School Library Journal, August 2014
Publisher's Weekly, June 2014
Kirkus Review, July 2014
3.8
K-3
Keywords: Irish Americans -- Illinois -- Chicago -- Juvenile fiction; Emigration and immigration -- Juvenile fiction; Lace and lace making -- Juvenile fiction; Chicago (Ill.) -- History -- 19th century -- Juvenile fiction; Irish Americans -- Fiction; Emigration and immigration -- Fiction; Lace and lace making -- Fiction; Chicago (Ill.) -- History -- 19th century -- Fiction; Irish Americans -- Fiction; Immigration and emigration -- Fiction; Lace and lace making -- Fiction; Chicago (Ill.) -- History -- Fiction; Picture books for children